WORKSHOP APPLICATION OF EXPERIMENTAL METHODS IN BIOLOGICAL LEARNING FOR MADRASAH TEACHERS IN WEST LOMBOK - Sukiman Sukiman; Immy Suci Rohyani; Kurniasih Sukenti; Evy Aryanti (Jurnal Warta Desa (JWD), 2021)
There are several learning models that are applied in learning Biology in secondary schools. The teaching and learning process in several schools is still dominated by the lecture method. This community service activity aims to improve the knowledge and skills of Madrasah Teachers in West Lombok Regency in applying experimental methods for learning biology on the subject of photosynthesis. The methods used in community service activities are: lectures and discussions,  practice photosynthesis experiments, and independent assignments in the form of making learning media. This community service activity was attended by 20 participants consisting of Madrasah teachers from West Lombok Regency. This activity received a positive response from the target participants. This activity has succeeded in increasing participants' knowledge and skills regarding the subject of photosynthesis and experimental methods for learning photosynthesis.